Assembly of silica nanoparticles based on stimuli-responsive covalent bonding between glycopolymers and poly(phenylboronic acid)s. (15th July 2020) - Li, Die; Miao, Ziyue; Bao, Chunyang; Xu, Xiaoling; Zhang, Qiang
Graphical abstract: Highlights: Surface-initiated Cu(0)-RDRP and click reaction are utilized to facilely immobilize glycopolymers and poly(phenylboronic acid)s brushes on the surface of silica nanoparticles. The formation of borate esters between glycopolymer and poly(PBA) induces extremely fast aggregation and total precipitation of nanoparticles in seconds. Compared with the linear polymers, the aggregated silica nanoparticles with borate ester linkages are more stable towards pH or monosaccharides. The glycopolymer-coated silica nanoparticles are capable of adsorbing boric acid from aqueous medium. Abstract: Covalent bonding between boronic acid and cis -diols is widely used to prepare stimuli-responsive nano materials. Herein, we report a kind of extremely rapid formation of boronate esters between glycopolymers and poly(phenylboronic acid)s for the assembly of silica nanoparticles. High-density poly(glycidyl methacrylate) brushes are first immobilized onto the surface of silica nanoparticles by surface initiated Cu(0) mediated reversible deactivation radical polymerization (SI-Cu(0)-RDRP). Subsequent post-polymerization modifications via click chemistry facilely fabricate the polymer scaffolds with pendent saccharides or phenylboronic acid (PBA) units. The rapid formation of boronate esters between glycopolymer and poly(PBA) induces further self-assembly and fast aggregation of nanoparticles. The sugar-containing boronate esters could survive under high temperature, excess monosaccharides and extreme pH. Hyper-cross-linked glycopolymer networks with tuned porous properties are prepared after etching of silica templates by hydrofluoric acid.